Study on the Evolution of Expressive Forms in Fu Zhongqi’s Urban-themed Ink Paintings from the Perspective of Art Semiotics (1985-2024) - Yang, Suyi (International Journal of Social Sciences and Public Administration, 2024)
This study adopts an art semiotic perspective to examine the evolution and transformation of expressive forms in Fu Zhongqi's urban-themed ink paintings from 1985 to 2024. Integrating art semiotic and iconographic theories, the research systematically reviews Fu Zhongqi's artistic achievements in urban-themed ink paintings and categorizes his works, while also providing an overview of the current research status. By conducting a comparative analysis of Fu Zhongqi's early, middle, and late-period works, this paper reveals the trajectory of his stylistic evolution and changes in expressive forms. The in-depth analysis of representative works such as "Last Year — The Wind of Harbin", "Accompanying the City", and the "Dusk" series highlights Fu Zhongqi's continuous innovation in techniques and his pursuit of free expression in urban-themed ink painting. The study further explores the underlying reasons for these transformations, including the influences of cultural context, artistic concepts, and social environment. Additionally, the paper forecasts potential future developments and challenges in Fu Zhongqi's urban ink painting, offering new perspectives and theoretical support for the study of urban-themed ink art.